Return to work - are we prepared for the future? Analysis of technological changes and future generations. (12th November 2014) - Upegui, Hector
Abstract : In addition to demographics and ongoing changes on structures of families and societies, the way in which persons are interacting with organizations is also changing. These interactions are defining service delivery and also the way in which we are and will be working. The power of digital information foster by cloud, mobility and social media is heavily influencing these changes. Twitter for instance, generates in one day more than 12 terabytes and Facebook more than 15 terabytes, while many organizations in the world are producing and processing petabytes of information. We are certainly facing a new way of doing things and a new work force generation with different values and certainly different ways of understanding prevention and rehabilitation. Do we need to add new strategies and data analysis to prevent accidents and diseases and to bring people back to work? How much information are we prepared to use to properly combine personal medical findings with socio-environmental variables? Can we see trends in our field or in other sectors that can show us where we might be heading? Where is the future heading? This presentation is about reflecting on some evidence with the aim of provoking discussions and motivate the participants to jointly keep on finding better ways to cope with the future.